68Ga-FAPI-46 PET/CT in a Metastatic Castration-Resistant Prostate Cancer Patient With Low PSMA Expression. (6th November 2022) - Aryana, Kamran; Manafi-Farid, Reyhaneh; Amini, Hamidreza; Divband, Ghasemali; Moghadam, Soroush Zarehparvar
Abstract: A 70-year-old man with mCRPC (metastatic castration-resistant prostate cancer) was referred for 68 Ga-PSMA PET/CT for restaging and the possibility of targeted molecular radioligand therapy with 177 Lu-PSMA. Numerous 68 Ga-PSMA–avid skeletal metastases with low SUVs were noted. Because of low PSMA expression, a 68 Ga-FAPI-46 PET/CT was performed to evaluate the eligibility for FAPI-based radioligand therapy. There were some discordant findings between 68 Ga-PSMA and 68 Ga-FAPI PET/CT scans regarding the detectability of lesions and SUVs. Our case signifies that 68 Ga-FAPI theragnostic may have a potential role in the treatment of mCRPC patients with insignificant PSMA expression or in cases after the failure of 177 Lu-PSMA therapy.